Tiv-jakun ethnic conflict in wukari district of taraba state northeast Nigeria: Horizontal inequalities approach - Joshua, Ruth Yohanna (2017)
Nigeria has witnessed several types of conflicts such as ethnic, communal and religious those are caused by certain factors. This issue is not far from Tiv-Jukun conflict which has long history of perennial conflict. The conflict has been described as the most violent dispute in No11h-East Nigeria since the Nigeria Civil War. The Tiv and Jukun have had a history of political and economic relegation; however, there has over the years been persistent conflict between the two ethnic communities who had lived peacefully in the recent time. From history the Jukun were the early settlers in Wukari, while the Tivs are considered immigrants and should not have right in Wukari local government. This study used horizontal inequality as a conceptual framework to examine the factors responsible for the ethnic conflict of Tiv - Jukun in Gidan idi Wukari of Taraba state north east Nigeria, focusing on the social-economic factors which were responsible for the conflict. Ten ( I 0) participants were involved in this study through interviews, using purposeful sampling and thematic analysis in order to obtain results. Finding shows there is horizontal inequality in education, economic and political factors between the Tiv-Jukun and none in-terms of health related matter. The impact of this conflict results in killing of people, huge burning of houses, business places, and schools, followed by looting of assets. The government set panel committee but could not settle the conflict. However this study recommends that there should be equal sharing formula in employment opportunities, education, and political positions. Land issue should also be addressed by making land a resource for mutual benefit.